FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN METODE KONTRASEPSI TUBEKTOMI PADA PASANGAN USIA SUBUR (Studi Kasus di Puskesmas Kec. Pontianak Kota) - Sufiati, Fitra Sawiyya; Mardjan, Mardjan; Saleh, Ismael (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Background: Contraception method is an effort to reduce the high number of mortality and morbidity caused by pregnancy. each method have the pluses and the minuses so simetimes it selection become a problem for fertile age couple. Tubectomy contraception is a long term contraception (permanent) and relatively has noside efect. Tubectomy contraception suggested for the fertile age couple who have minimally 2 kids and the age of the mother 26 years old above. it’s because pregnancy that happen in fertile age couple over than 26 years old has a high risks and also the mother is very susceptible towards disease. There was a significant improvement in Indonesia MMR from 228 (2007) to 359 (2012) per 100,000 live births. The use of contraceptive methods in particular steady Operations Women (MOW) in Puskesmas Kampung Bali during the year 2010 to the year 2011 and in 2012 had a significant decrease of 8.8%, 1.9% to 0.3%. Users tubectomy at the City Health Center Kec.Pontianak 59 cases.Aim: The purpose of this study was to determine the risk factors (economic, social and cultural (beliefs) and husband's support) with the selection of contraceptive methods tubectomy in fertile couples in Kec. Pontianak City Health Center.Method: This study is an observational analytic study with case-control study design. Analysis of the data in the study covers univariate and bivariate analysis. the sample size in this study is as much as 66 respondents (22 cases and 44 controls). Statistic test using chi-square test bivariate analysis with significant standart 95% and using Odds Ratio (OR) to know the number of the risk.Results: The results showed that there is a relationship between economic factors(p 0.000), sociocultural (trust) (p 0.034), support the husband (p 0.000) with the selection tubectomy contraception in Kec. Pontianak City Health Center.Suggestion: The health workers and family planning field workers are expected to play an active role in increasing the awareness of fertile age couples by providing a sustainable extension to the community in order to increase their participation in unsing tubectomi.Key words: Economic Factors, Socio-cultural, husband support